PENGEMBANGAN MODUL BERBASIS HOTS PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Nining Nakhliyati; M. Taufik, M.Pd; Dr. Ratna Sari Dewi, M.Pd (LPPM Universitas Cipta Mandiri, 2025)
The learning process carried out at SDN Margasari class V in science and science subjects is mostly teacher-centred using the lecture method. The high-level thinking abilities of class V students at SDN Margasari are also not visible. This is proven by the absence of interactions such as questions and answers between students and teachers, as well as the absence of activities that lead to higher level thinking such as analyzing, evaluating or creating activities. This research is research and development (R&D) which aims to develop a HOTS-based module on science subjects, material like what is my regional culture, this research is also to find out the quality of the HOTS-based science module that was developed, and find out students' responses after using this module. The subjects of this research were 20 class V students at SDN Margasari. The assessment results in this research were 89% from material experts, and 84.00% from media experts, overall getting a score in the